The Correlation between Students’ Metacognitive Strategy and their Reading Comprehension in Higher Education - Siti Nurul Ilmi Haling (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
Numerous studies have been undertaken on metacognitive awareness and reading comprehension at the secondary school level. Consequently, this study focuses on these characteristics within the higher education level. This study aims to reveal students' metacognitive awareness in reading strategies, the levels of their reading comprehension, and how these two variables are correlated in higher education. To achieve the mentioned objectives, quantitative method, particularly descriptive and correlational approaches were employed. This study's sample consisted of the fifth-semester English Education students at IAIN Bone throughout the 2020/2021 academic year. Cluster random sampling is the sampling method utilized in this study. In order to collect the necessary data, two instruments were used, which were questionnaire to reveal students’ metacognitive reading strategy, and reading test to find out students’ reading comprehension. The result showed that most students routinely employed reading strategies while reading English material, and among the three metacognitive reading strategies, Problem-solving Reading Strategies was the most popular option. Besides, the result indicates that students' reading comprehension is characterized as weak. Furthermore, students’ metacognitive reading strategy has an effect on reading comprehension since they involve the use of self-awareness and intentional motivation to employ one or more techniques for keeping tabs on how well one is grasping what they're reading. It can be concluded that students who employ metacognitive reading strategy have a greater chance of understanding a text, when compared to students with poor metacognitive reading strategy.